The role of endoscopic ultrasound in the diagnosis and characterization of focal liver lesions - Ahmed Morad Hashim; Gamal Eldin Mansour Mohamed Gamal; Abeer Abdellatef; Hany Hagag Ahmed (The Egyptian Journal of Internal Medicine)
Abstract Background Incidentally discovered focal liver lesions (FLLs) are a common reason for referral to hepatobiliary services. These lesions are frequently found in patients with colorectal cancer, cirrhosis, or incidentally during evaluations for abdominal pain or shock. Several established diagnostic tools such as magnetic resonance imaging (MRI), transabdominal ultrasound (US), and computed tomography (CT) are well-studied for assessing liver diseases. Endoscopic ultrasound (EUS), traditionally used for evaluating the mediastinum, biliary tract, esophagus, stomach, and pancreas, is increasingly complementing these traditional diagnostic methods in hepatology. The study aimed to delineate the endoscopic ultrasound elastography role in visualization and hepatic focal hepatic tissue differentiation of lesions in comparison to the routine radiological and laboratory methods. Methods A cross-sectional study was conducted, we enrolled 41 patients with hepatic focal lesions, abdominal ultrasonography, triphasic CT abdomen, and Endosonography examinations were performed on all participants. Results There was a highly significant difference between the studied groups as regards the Strain Ratio and Echogenicity (P0.01). Conclusion Ultrasound elastography and strain ratio are promising, non-invasive, nondependent on any contrast material techniques that could significantly enhance routine grey-scale sonographic examinations of the liver by better delineating the characteristics of hepatic focal lesions.